CORPORATE GOVERNANCE OF ISLAMIC BANKING IN MALAYSIA: A LITERATURE REVIEW - Samri, Norizan; Hashim, Roslina; Jakaria, Noor Azizah; Baba, Rozita (Jurnal ’Ulwan, 2020)
Corporate governance basically involves balancing the interests of the many stakeholders in a company including its shareholders, management, customers, suppliers, financiers, government and the community. Corporate governance also provides the framework for managing a company’s objectives; it involves practically every area of management, from action plans and internal controls to performance measurement and corporate disclosure. Given the phenomenal increase in Islamic banking activities globally, it is important that there exists good governance practices of Islamic financial institutions (IFIs). This is primarily to ensure its sustainability in the long run. More importantly, in order for Islamic banks to play an optimum role in the development of Islamic countries, it is imperative to develop regulatory structures which can help to control fraud, exploitation, and non-compliant behavior in banking practices. This paper discusses an overview of corporate governance and shariah governance. Corporate governance challenges to Islamic Financial Institutions are also elaborated.